The Notions of Dār al-Ḥarb and Dār al-Islām in Islamic Jurisprudence with Special Reference to the Ḥanafī School - Ahmad, Muhammad Mushtaq (Islamic Studies, 2008)
The article argues that the bifurcation of the world into two domains—Dar al-Islām and Dār al-Ḥarb—is essentially an affirmation of the principle of territorial jurisdiction. This principle was enunciated with a high degree of clarity and its implications were worked out with rigour and consistency by the Muslim jurists, especially those of the Ḥanafī school. Among the reasons that have mainly led to confusion and misgiving on the question are: (i) The use of the term Dār al-Ḥarb gave rise to the impression that hostility should inform the relations between Dār al-Islām and all other entities. (ii) The firmness shown by the Prophet (peace be on him) during the last years of his life to root out the forces actively inimical to Islam and establish a secure foothold for Islam in the Arabian peninsula has at times been detached from its space-time context and considered to be the norm for the Muslims in their relationship with all non-Muslim entities. The paper argues that seventh century Arabia was a very special case and Muslim jurists, especially Ḥanafī jurists, consider it sui generis which may not be extended beyond its space-time context. The general principle guiding Muslims in their relationship with non-Muslim entities remains that the Muslims may engage in fighting against the non-Muslims who are belligerent towards them, rather than against non-Muslims qua non-Muslims.